BIOMARCADORES DA NEMATODIOSE GASTRINTESTINAL EM BOVINOS DE CORTE CRIADOS A PASTO EM UMA REGIÃO DE CLIMA TROPICAL - Vinicius Duarte Rodrigues (2023)
Biomarkers are specific conditions during the normal or pathogenic biological process, which can assist in the diagnosis of diseases. Some biomarkers, such as pepsinogen, have already been well standardized for taurine cattle infected by Ostertagia sp. and raised in regions with a temperate climate, however, there is still no information on its use in zebu cattle predominantly infected by Cooperia sp. and Haemonchus sp. Therefore, the objectives of this project were to evaluate probable biomarkers, which can differentiate animals that are carriers and non-carriers of gastrointestinal nematodes (NGIs) and evaluate correlation with indicators of infection and animal health. In the first stage, a biomarker was defined that differentiated the groups. 36 Nelore cattle, males and females aged between 10 and 18 months, were selected, kept in the same paddock with water, mineral supplementation ad libitum and naturally infected by NGIs. They were distributed in a randomized block design into two groups, based on the examination of eggs per gram of feces (OPG), sex, weight, blood count and serum biochemistry on day -14, to which the following treatments were drawn: treated with anthelmintic (TRAT A) and not treated with anthelmintic (CON A). On days 0, 7, 14, 21, 28, 42 and 56, only the TRAT group was administered a dose of fenbendazole 5mg/kg, orally. On the same dates, feces were collected and OPG was evaluated using the Mini-FLOTAC technique, blood collection was collected to evaluate blood count, serum biochemistry and possible biomarkers (phosphorus, gastrin and pepsinogen). In the second stage, the biomarker that differentiated the TRAT A and CON A groups was evaluated, in this case pepsinogen. 75 male Nelore cattle, aged between 12 and 24 months, were selected, separated into a randomized block design, based on OPG, using the McMaster technique and weight on day 0 and distributed into three groups: not treated with anti-helmintic (CON BC), treated with Moxidectin 0.2 mg/kg B.V. (TRAT B) and treated with a combination of Ivermectin (0.2 mg/kg B.V.) and Albendazole Sulfoxide (2.5 mg/kg B.V.) (TRAT C). Pepsinogen levels were assessed on days 0 and 28. In the first stage, the results of weight, albumin, hematocrit (VG), erythrocytes and hemoglobin showed no difference between the groups; and there was a negative correlation between VG and albumin with pepsinogen, and albumin showed a negative correlation with the percentage of Haemonchus sp. in coproculture. Among the biomarkers, only pepsinogen differentiated TRAT A and CON A from the 28th day of the study. This was also repeated in the second stage, in which the TRAT B and TRAT C groups showed a decrease in pepsinogen values after anthelmintic treatment. Therefore, it is clear that pepsinogen is a promising biomarker in the diagnosis of NGIs and in the evaluation of anthelmintic treatments in cattle raised on pasture in central Brazil.